How DNS Misnaming Distorts Internet Topology Mapping - Zhang, Ming; Ruan, Yaoping; Pai, Vivek; Rexford, Jennifer (USENIX Annual Technical Conference, 2006)
Network researchers commonly use reverse DNS lookups of router names to provide geographic or topological information that would otherwise be difficult to obtain. By systematically examining a large ISP, we find that some of these names are incorrect. We develop techniques to automatically identify these misnamings, and determine the actual locations, which we validate against the configuration of the ISP's routers. While the actual number of misnamings is small, these errors induce a large number of false links in the inferred connectivity graph. We also measure the effects on path inflation, and find that the misnamings make path inflation and routing problems appear much worse than they actually are.